Progressive Ovarian Cancer with Trocar Site Metastases Resulted from Inadequate Laparoscopy - Sigit Purbadi; Ina Damayanti (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: Discuss the complications of laparoscopic ovarian cystic neoplasms. Method: Case report A-52 year old female with 2 parities, complained of a lump at anterior abdominal wall during chemothe rapy for clear cell ovarian adenocarcinoma after total hysterectomy and bilateral salphingooophorec tomy by lapa roscopy. The indication was suspected ovarian cancer from solid parts found during ultrasound and CA125 level 169. During previous laparoscopy, the cyst was ruptured, left in abdominal cavity with high C02 pressur e for five hour s and retrieved without a bag.The frozen section examination of the cyst wallwere diagnosed as endometriosis.The physician assured her that the lump was only scar and did not need further evaluation. CA125 level was 557 IV after chemotherapy. PET scan confirmed a 2 ern-diameter mass superior to periton eum and multiple implants intra abdominally. Result: Adebulking laparotomy was done. Omental cake was found with one part adhered to the right previous trocar insertion site. It was connected to tumor implant size 3x4 em until fat tissue of abdomen wall.Another implant was also found at left para colical area . Conclusion: Laparoscopy offers advantages such as less bleeding, better visualisation, and enhanced recovery. Some controversies exist in cases with suspicion of malignancy. Pneumoperitoneum might cause seeding of tumor cells. This could be prev ented by using low pressure, avoidance of exsuflation of gas through tro car opening, or by using bags to retrieve operative specimens. Preoperative evaluation of clinical findings, ultra sound, and tumor markers are important to prevent improper surgical management. Keywords: complication, laparoscopy, metasta ses, ovarian cancer, trocar site.